The Influence of Green Recruitment and Green Selection on the Institutional Attractiveness of Prospective StudentsThe Influence of Green Recruitment and Green Selection on the Institutional Attractiveness of Prospective Students - Fawaid, Akh (GREENOMIKA, 2025)
Intense competition among higher education institutions and weak institutional differentiation in student admissions have become challenges for STIE Bakti Bangsa. Admission practices that lack integration of sustainability values are considered insufficient to attract prospective students. Therefore, the implementation of Green Human Resource Management (GHRM),particularly through Green Recruitment and Green Selection, is viewed as a necessary environmental-based differentiation strategy. This study aims to analyze the simultaneous and partial effects of Green Recruitment and Green Selection on prospective students’ Institutional Attractiveness. The study employs a quantitative associative approach, with data collected through questionnaires and analyzed using multiple linear regression. The results indicate that Green Recruitment and Green Selection simultaneously have a significant effect on Institutional Attractiveness, while partially Green Selection shows a more dominant influence. These findings confirm that GHRM practices play a strategic role in enhancing institutional attractiveness and strengthening sustainability-based student admission competitiveness.